Factors restraining Female Workers from joining Pharmaceutical Firms: Evidence from local Pharmaceutical Industry in Badin - Rustamani, Shahid Ahmed; Shah, Syed Abdul Sattar; Bhatti, Khalil U Rehman (Annals of Human and Social Sciences, 2024)
The study is aimed to ascertain the variables affecting willingness to join pharmaceuticals i.e. cultural barriers, relocation, interpersonal relation. Statistical tools including normality of data, regression, standard deviation using SPSS software. The study provided conclusive grounds that significant perceived impact of interpersonal relations with boss on readiness/willingness of female professionals to join pharmaceuticals industry , cultural barrier significantly impact on readiness/willingness of female professionals to join pharmaceuticals industry , there is significant perceived impact of relocation /travelling on readiness / willingness of female professionals to join pharmaceuticals industry, female professionals at pharmaceutical industry face challenges in maintaining interpersonal relations with clients, besides they are significantly concerned over interpersonal relations with colleagues/staff. It was found that there is significant impact of interpersonal relations with boss on willingness of female professionals to join pharmaceuticals industry.